Persistence Statements: Describing Digital Stickiness. (14th August 2017) - Kunze, John; Calvert, Scout; DeBarry, Jeremy D.; Hanlon, Matthew; Janée, Greg; Sweat, Sandra
In this paper we present a draft vocabulary for making "persistence statements." These are simple tools for pragmatically addressing the concern that anyone feels upon experiencing a broken web link. Scholars increasingly use scientific and cultural assets in digital form, but choosing which among many objects to cite for the long term can be difficult. There are few well-defined terms to describe the various kinds and qualities of persistence that object repositories and identifier resolvers do or don't provide. Given an object's identifier, one should be able to query a provider to retrieve human- and machine-readable information to help judge the level of service to expect and help gauge whether the identifier is durable enough, as a sort of long-term bet, to include in a citation. The vocabulary should enable providers to articulate persistence policies and set user expectations.